Compound Heterozygous Protein C Deficiency Caused by Two Mutations, Arg-178 to Gin and Cys-331 to Arg, Leading to Impaired Secretion of Mutant Protein C - Sugahara, Yuichi; Miura, Osamu; Hirosawa, Shinsaku; Aoki, Nobuo (Thrombosis and Haemostasis, 1994)
The protein C gene in a patient apparently homozygous for protein C deficiency was analyzed. Two different point mutations, each located in a different allele, were detected to reveal that the patient is a compound heterozygote. Mutation of Arg-178 (CGG) to Gin (CAG) [mutation I] was detected in exon VII, in the vicinity of activation peptide cleavage site by thrombin. Mutation of Cys-331 (TGC) to Arg (CGC) [mutation II] was found in exon IX, at one of the sites involved in disulfide bond formation in the catalytic domain of the heavy chain. The alteration of Cys-331 to Arg disables the formation of the disulfide bond and would alter the protein conformation. Transient expression assays using COS-7 cells transfected with protein C expression vectors containing each one of these two mutations suggested that each of the two mutations would lead to the protein C deficiency by an impairment of secretion of the respective mutant proteins.